2018
DOI: 10.1080/15384101.2018.1489177
|View full text |Cite
|
Sign up to set email alerts
|

EGFR activation induced Snail-dependent EMT and myc-dependent PD-L1 in human salivary adenoid cystic carcinoma cells

Abstract: Epithelial-to-mesenchymal transition (EMT) confers cancer cells the ability of invasion and metastasis. However, how does EMT contribute to evasion of immune surveillance is unclear, especially in salivary adenoid cystic carcinoma (SACC). In this study, we investigated the molecular link between EGF-induced EMT and the immune checkpoint ligand programmed death-ligand 1 (PD-L1) by immunoprecipitation (IP) and Westernblot analysis. Cell migration and invasion activity was assayed by transwell assay. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…Chen et al [105] demonstrated that EMT positive human esophageal cancer tissues had higher PD-L1 expression compared to an EMT negative subgroup. Similar studies have shown an association between EMT and immune checkpoint expression in several cancers including thymic carcinoma [106] , melanoma [107] , adeno cystic carcinoma [108] , extrahepatic cholangiocarcinoma [109] and renal cell carcinoma [110] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapysupporting
confidence: 62%
See 1 more Smart Citation
“…Chen et al [105] demonstrated that EMT positive human esophageal cancer tissues had higher PD-L1 expression compared to an EMT negative subgroup. Similar studies have shown an association between EMT and immune checkpoint expression in several cancers including thymic carcinoma [106] , melanoma [107] , adeno cystic carcinoma [108] , extrahepatic cholangiocarcinoma [109] and renal cell carcinoma [110] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapysupporting
confidence: 62%
“…Another study in lung cancer demonstrated that p-Smad2 dependent TGF-β signalling is involved in PD-L1 overexpression [101] . Epidermal growth factor also induced EMT and PD-L1 expression in breast cancer and salivary adenoid cystic carcinoma cells [108,112] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapymentioning
confidence: 94%
“…Furthermore, PD-L1 can indirectly activate p38 through DNA-PKcs, which promotes chemoresistance (Wu et al, 2018), and therefore suggests a common feed forward loop that may connect PD-L1 expression, DNA repair and pro-metastatic pathways (Goodwin et al, 2015), and convergent p38 activity. Interestingly, PD-L1 expression in the tumor and tumor microenvironment is also associated with poor outcomes and an aggressive and metastatic phenotype in many cancer subtypes (Kim et al, 2016; Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…eMT status is closely associated with cancer metastasis, stemness, immune escape and drug resistance in HCC (17,18). It was previously identified that eMT is involved in the regulation of Pd-l1 in several cancer types, including breast cancer (19,20), lung cancer (17,21), pancreatic cancer (22), esophageal cancer (23) and salivary adenoid cystic carcinoma (24). The authors previously demonstrated that eMT is associated with Pd-l1 expression in patients with Hcc (8).…”
Section: Tnf-α-mediated Epithelial-to-mesenchymal Transition Regulatementioning
confidence: 99%